2011
DOI: 10.5950/0738-1360-26.3.233
|View full text |Cite
|
Sign up to set email alerts
|

Valuing Bag Limits in the North Carolina Charter Boat Fishery with Combined Revealed and Stated Preference Data

Abstract: We use telephone survey data on charter boat anglers to estimate demand models to value snapper-grouper and king mackerel bag limits in the North Carolina forhire fishery. The telephone survey presents respondents with hypothetical situations about higher charter fees and lower snapper-grouper and king mackerel bag limits and asks about the number of trips they would take in each situation. Stated preference trip responses are used in a jointly estimated revealed and stated preference demand model. We find tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…Demographic data such as sex, age, postal code and nationality are also useful. Although some of the information that is collected above can be gleaned from the app data, a short survey will provide insight into stated versus revealed preference (Whitehead et al 2011), and help to track changes in demographics and behaviour over time (Ditton et al 1992), which can be useful when collecting, analysing and correcting for interangler variability in catch rates and, more generally, angler behaviour and motivation. For example, anglers could report the number of years that they have been angling.…”
Section: Angler Demographics and Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Demographic data such as sex, age, postal code and nationality are also useful. Although some of the information that is collected above can be gleaned from the app data, a short survey will provide insight into stated versus revealed preference (Whitehead et al 2011), and help to track changes in demographics and behaviour over time (Ditton et al 1992), which can be useful when collecting, analysing and correcting for interangler variability in catch rates and, more generally, angler behaviour and motivation. For example, anglers could report the number of years that they have been angling.…”
Section: Angler Demographics and Behaviourmentioning
confidence: 99%
“…Other potential questions include preferred gear type, the importance of fishing relative to other leisure activities (which is another window into specialization; Ditton et al 1992), and membership in fishing clubs (which will allow managers to generate specialized reports and form partnerships that encourage recruitment and retention). Although some of the information that is collected above can be gleaned from the app data, a short survey will provide insight into stated versus revealed preference (Whitehead et al 2011), and help to track changes in demographics and behaviour over time (Ditton et al 1992), which can be useful when collecting, analysing and correcting for interangler variability in catch rates and, more generally, angler behaviour and motivation. The survey should be designed in consultation with the appropriate experts, and anglers should be invited to update their responses periodically (e.g.…”
Section: Angler Demographics and Behaviourmentioning
confidence: 99%
“…Hesseln et al (2003) reported that immediately after a crown fire, consumer surplus per trip equaled $90 for hikers and $10 for mountain bikers. Finally, Whitehead et al (2008a) reported estimates of consumer surplus per trip of approxi mately $90 for visits to North Carolina beaches, while Whitehead et al (2011) reported an estimate of consumer surplus per trip of $273 for recreational grouper, king mackerel, and snapper fishing in North Carolina. It should be noted, however, that the results of this study are not directly comparable to any of those referred to above.…”
Section: Model Specification and Regression Resultsmentioning
confidence: 99%
“…They were concerned with the impact of improved access to beaches and increasing the average width of beaches on the net benefits accruing to visitors. They estimated a randomeffects Poisson model and found that while hypothetical bias was reflected in the SP data, it did not have a statistically significant impact on estimates of consumer surplus per trip.12 Whitehead et al (2011) considered changes in the net benefits from recreational fishing; they also utilized Englin and Cameron's (1996) framework. Their issue of particular concern was the impact of a simultaneous increase in the boat charter fee and decrease in the bag limit for either snapper-grouper or king mackerel.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Head boats carry more passengers and operate on a posted schedule. Whitehead et al (2011) use data from a follow-up telephone survey of a subsample of these charter anglers to estimate demand models to value snapper-grouper and king mackerel bag limits in the North Carolina for-hire fishery.…”
Section: Introductionmentioning
confidence: 99%